The exchange rate susceptibility of European core industries, 1995-2010 - David Leuwer; Bernd Süßmuth (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2017)
This study investigates reactions to real exchange rate changes in the German, French and UK automobile and mechanical engineering sectors using monthly data from 1995 to 2010. Our findings indicate that EUR/USD appreciations hamper exports, but do not necessarily imply an aggravated business climate or export order-book assessment. This does not apply to the GBP/USD and corresponding time series for the UK. First and foremost, our fixed coefficient and time varying parameter VAR model estimates confirm the extraordinary role of the German key sectors, while currency union membership seems to play a minor role at best. Overall, the exchange rate susceptibility is less profound than claimed by lobbies and held as popular belief.
Keywords: C30; E42; F41; 330; exporting sectors; confidence indicators; structural VAR